Analysis of M/G/1 Feedback Queue under Steady State When Catastrophes Occur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we analyse the M/G/1 feedback queue under steady states conditionswhen catastrophe occur. The stationary probability of  ‘n’ and zero customers sins the system are derived. The asymptotic behaviour of the model and the averages queues lengthare also obtained. The numerical example  are provided  to   test the feasibility of the model.